Agricultural waste pulverised biomass: MEC and flame speeds. (July 2015) - Saeed, Muhammad Azam; Medina, Clara Huéscar; Andrews, Gordon E.; Phylaktou, Herodotos N.; Slatter, David; Gibbs, Bernard M.
Abstract: A modified Hartmann dust explosion tube was employed to determine the Minimum Explosible Concentration (MEC) and the flame speed for three Pakistani agricultural wastes: bagasse, rice husk and wheat straw. Agricultural biomass had a higher ash content than for woody biomass and this influenced the MEC. The dispersion, ignition and MEC were influenced by the particle size distribution, as also demonstrated by high speed video. There was a strong linear correlation between the MEC and the sum of the ash and moisture content of these and other biomasses, indicating that this inert mass in the particles acted to reduce the flame temperature and reduce the lean flammability limit or MEC. Comparison of the results was made with non-agricultural waste pulverized biomass. Peak flame speeds were approximately 2.5 m/s. The lean limits for these pulverised agricultural waste biomasses were comparable to that of pulverised wood but were much leaner than those for coal and hydrocarbon fuels, which indicate that these biomasses are highly reactive. Highlights: Agricultural wastes biomass residues as a potential fuel for extraction of energy. Explosibility properties of pulverised crop residues are comparable to wood fuel as measured using modified Hartmann. Strong dependence of size of the particles and the %ash + moisture contents on the sensitivity of ignition. Photographic study to demonstrate the distribution of particles and propagation of flame in fine and coarse size range fractions.